1974
DOI: 10.1007/bf00022478
|View full text |Cite
|
Sign up to set email alerts
|

General and specific combining ability in lucerne at different levels of in breeding and performance of second-generation synthetics measured in competitive conditions

Abstract: In a breeding program of luceme based on selfing in sward conditions general as well as specific combining ability was evaluated for diallel crosses made at different levels of inbreeding. The performance of the second generation synthetics was studied as well. The efficiency of selting and subsequent selection in improving the genetic value of parents is very important. The optimal solution for luceme breeding could well be the use of synthetic varieties which are based on 4 inbred clones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…For what total green matter yield per m 2 is concerned, seed producer plants yielded 65 %, 76 % and 73 % of the total in mixtures A, B and C respectively. These results confirm that, under dense stand conditions, plants superior in height, which is one of the most powerful characters governing competitive ability (ROTILI & ZANNONE, 1974ZANNONE, , 1975 YAMADA & HO RI UCHI, 1960) are the most productive both in forage and in seed.…”
Section: Methodssupporting
confidence: 64%
“…For what total green matter yield per m 2 is concerned, seed producer plants yielded 65 %, 76 % and 73 % of the total in mixtures A, B and C respectively. These results confirm that, under dense stand conditions, plants superior in height, which is one of the most powerful characters governing competitive ability (ROTILI & ZANNONE, 1974ZANNONE, , 1975 YAMADA & HO RI UCHI, 1960) are the most productive both in forage and in seed.…”
Section: Methodssupporting
confidence: 64%
“…Nevertheless, Rotili and Zannone [5] testified the advisability of bringing the inbred line up to the second and third generations (J 2 and J 3 ). This research is devoted to the selection processes of alfalfa to isolate the valuable samples and on their basis create inbred lines for inclusion in newly synthesized populations (varieties).…”
Section: Results Of Selection Studies Of Alfalfa Based On Inbred Linementioning
confidence: 99%
“…A formal comparison of HS progeny‐based vs. S 2 progeny‐based selection was hardly provided by earlier studies. For example, the reports by Rotili and Zannone (1974) and Rotili (1976) compared the phenotypic selection of S 0 , S 1 , S 2 , S 3 and/or S 4 individual plants of alfalfa grown in density conditions by assuming additional, highly‐intense selection for plant vigor performed after each selfing stage (e.g., selecting among S 1 plants generated from selfed selected S 0 plants), thereby highlighting the ability to realize further selection gain over that of the preceding generation until the S 2 generation. In addition, their studies were based on narrowly‐based synthetic varieties of two, four or eight selected parents, a scenario that can emphasize the impact of inbreeding depression and the value of selecting against it within selfed progenies.…”
Section: Discussionmentioning
confidence: 99%
“…Half-sib progeny-based and S 1 progenybased selections were equally ineffective for alfalfa in Busbice et al (1974). Rotili and Zannone (1974) and Rotili (1976) found that alfalfa yield gains tended to be maximized by selection on S 2 material that derived from earlier selection performed at each selfing stage. One cycle of S 1 progeny-based selection was as effective as two cycles of mass selection and more effective than one cycle of S 2 progeny-based selection in a more recent alfalfa study (Hansen et al, 2010).…”
mentioning
confidence: 99%